The Effect of Work Environment and Motivation on Performance of Teachers in Islamic Education Institution - Abd. Rahman Alatas; Hartanto Hartanto; Rachmad Ilham; Slamet Riyadi; Musran Munizu (Departement of Mathematics Education, 2023)
The goal of this study is to clarify how motivation and workplace conditions affect teachers' effectiveness. This is a quantitative type of study. Teachers of private schools made up the population analyzed for this study. Purposive sampling, which was given to 82 respondents, was utilized to acquire the data. The SPSS 24 program was used to perform multiple linear regression analysis on the data collected in this study utilizing questionnaires and documents. According to the study's conclusions, both motivation and the workplace environment have a significant impact on teachers' performance. Motivation and the work environment account for 13.9% of the adjusted R-square, which is 0.139. Motivation has a significant impact on teachers' performance; however, the work environment has no significant impact.